INTERVENSI GURU KELAS UNTUK MENANGANI SISWA BERMASALAH DI SEKOLAH DASAR - Nina Mekalungi; Supriyono; Rasyidah; Hanifa; Zunan Azis; Choiriyah Widyasari; Ernawati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This study aims to explore the techniques and strategies used by classroom teachers to handle problem students at Madrasah Ibtidaiyah Miftahul Ulum Sidowungu. This qualitative research utilized data collection methods including classroom observations, in-depth interviews with teachers, and document analysis. The findings indicate that teachers employ various effective techniques, including personal approaches, reward and punishment systems, and adjustments in teaching methods. Positive approaches emphasizing rewards and active collaboration with parents have proven significant in reducing problematic behaviors. Social-emotional skills training also plays a crucial role in supporting students' emotional management and social interactions. However, there are hindering factors such as limited resources, lack of parental support, and students' mental health issues that affect the effectiveness of the applied strategies. Supporting factors, such as school management support and available programs, positively contribute to the success of handling techniques. This research provides insights into best practices for managing problem students and is expected to serve as a reference for other educational institutions to enhance classroom management and support students' optimal development.